Advancing dementia care in Pakistan: challenges and the way forward - Ali, Soha; Zehra, Maha; Fatima, Tehreem; Nadeem, Abdullah (Frontiers in Dementia, 2023)
Dementia encompasses a wide range of cognitive and psychological impairments that hinder individuals' ability to carry out daily tasks effectively. In the context of Pakistan, the prevalence of dementia patients currently stands at approximately 150,000-200,000, reflecting the impact of the country's significant population size. This increase in numbers poses a substantial socioeconomic challenge, emphasizing the need to prioritize dementia within Pakistan's healthcare system. However, the allocation of resources and attention to dementia remains relatively low, leading to considerable difficulties in both diagnosing and treating affected individuals. The provision of comprehensive dementia care faces numerous obstacles, including limited public awareness, insufficient research initiatives, inadequate infrastructure, and a lack of specialized training programs. To address these challenges, the Pakistani government must acknowledge and address the stringent regulations governing the neuroscience industry, with a specific emphasis on catering to the unique needs of dementia patients. By doing so, they can ensure the delivery of high-quality care, essential support, and necessary resources for individuals living with dementia in the country.